2022
DOI: 10.1111/basr.12291
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employee turnover on the financial performance of microfinance institutions: A global evidence

Abstract: Microfinance is a preferred development tool in many developing countries around the world; however, the industry has been facing many challenges in recent years, including the attainment of financial sustainability. Therefore, this study is aimed at investigating the effect of employee turnover on the financial performance of microfinance institutions (MFIs). The study utilized unbalanced panel data of 1561 unique MFIs from 2010 to 2018. The data were then analyzed by conventional econometric techniques such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…The findings may indicate that the level of turnover may not have reached the threshold in our sample, resulting in the inexistence of a significant non-linear relationship (Model-5, Table 3). This finding is consistent with the study of Mia et al (2022a), which found the non-linear effect of employee turnover on the financial performance of MFIs. While these findings contradict most of the existing literature, they can be explained in several ways.…”
Section: Baseline Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The findings may indicate that the level of turnover may not have reached the threshold in our sample, resulting in the inexistence of a significant non-linear relationship (Model-5, Table 3). This finding is consistent with the study of Mia et al (2022a), which found the non-linear effect of employee turnover on the financial performance of MFIs. While these findings contradict most of the existing literature, they can be explained in several ways.…”
Section: Baseline Resultssupporting
confidence: 93%
“…It can, therefore, be concluded that the body of academic discourse on employee turnover is growing but limited in the microfinance context. Besides, except for the recent study of Mia et al (2022a), the majority of the previous studies have only explored the turnover-financial performance nexus in the context of industries other than MFIs [ (Hancock et al, 2013) and the reference list therein]. In their study, Mia et al (2022a) found that employee turnover has a negative effect on the financial performance of MFIs, although the outcomes vary with the modelling, sub-sample and other factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across several developing countries, the microfinance model is the preferred development tool (Mia, Ahmad & Halim, 2022). Several African countries have experienced significant growth in the microfinance sector and it was documented that more than 100 million customers take up micro loans across the region (Madialo, 2022).…”
Section: Introductionmentioning
confidence: 99%